2012
DOI: 10.1038/srep00256
|View full text |Cite
|
Sign up to set email alerts
|

Rare coding SNP in DZIP1 gene associated with late-onset sporadic Parkinson's disease

Abstract: An association between a rare, coding, non-synonymous SNP variant in the gene DZIP1 and Parkinson's disease was found, based on an analysis of the existing NGRC genome-wide association study dataset. The statistical analysis utilized the hypothesis-rich, targeted search unbiased assessment approach, rather than the hypothesis-free, genome-wide agnostic search paradigm. The association of DZIP1 with Parkinson's disease is discussed in the context of a Parkinson's disease stem-cell ageing theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The realistic trajectory of NO x reflects a compilation of environmental policies and economic activities 29 . NO x emissions in many industrialized countries are expected to decrease 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The realistic trajectory of NO x reflects a compilation of environmental policies and economic activities 29 . NO x emissions in many industrialized countries are expected to decrease 30 .…”
Section: Discussionmentioning
confidence: 99%
“…NO x emissions in many industrialized countries are expected to decrease 30 . For example, the NO x reductions in Europe in 2010 can be partly attributed to the global economic recession, and partly to the European NO x emission controls 29 . Due to rapid economic development and the coal-dominated energy consumption structure, however, large increases in NO x from China have persisted over the past several decades 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in 13 genes have been associated with these Mendelian inheritable cases of PD, via familial genetic linkage studies. For non-monogenic PD, dozens of single-nucleotide polymorphisms (SNPs) risk factors have been identified based on Genome-Wide Association Studies (GWASs) (2,3,4). Likewise, a number of environmental risk factors (e.g., exposure to metals and pesticides) have been uncovered by epidemiological studies (5).…”
Section: Introductionmentioning
confidence: 99%
“…We have proposed an alternative theory on the origin of sporadic PD, which we term here the Hematopoietic Origin Theory (HOT) (3,16,17). Sporadic PD would be characterized by two phases: an induction phase, followed by a systemic propagation phase.…”
Section: Introductionmentioning
confidence: 99%
“…A new study by Xiao et al 72 found hematologic abnormalities in alpha-synuclein knock-out mice indicative of a role of alphasynuclein in late-stage hematopoiesis. A genome-wide association study found that a rare nonsynonymous mutation in DZIP1 is a risk factor for PD 73 . DZIP1 is a component of the Hedgehog signaling pathway 74 .…”
Section: A Site Of Origin For the Pd-statementioning
confidence: 99%